EFFECTIVENESS OF SINGLE CHEST TUBE VS DOUBLE CHEST TUBE DRAINAGE APPLICATION INPATIENTS UNDERGOING DECORTICATION: A RETROSPECTIVE STUDY. - Singh, Sudhanshu; m.G. Rayee; S.C. Jha (Student’s Journal of Health Research Africa, 2024)
Background Chest tube drainage is essential following decortication for stage III empyema thoracis. While double chest tube placement is widely used, a single chest tube may offer comparable efficacy with reduced postoperative pain. This study evaluates the effectiveness of chest tube drainage and double chest tube placement. Methods A retrospective comparative study was conducted on 84 patients at Patna Medical College and Hospital from November 2021 to November 2024. Patients were randomly assigned to either single (Group A) or double (Group B) chest tube drainage. Primary outcomes included total drainage volume, duration of drainage, and pain scores, while secondary outcomes were air leaks, chest tube reinsertion, and hospital stay. Data were analyzed using SPSS, with statistical significance set at p<0.05. Results Group A had a higher total drainage volume (1200 mL vs. 500 mL) and lower pain scores (2 vs. 3) than Group B. Drainage duration was longer in Group B (5 vs. 4 days), but both groups had similar hospital stays (6-7 days). No reinsertion of chest tubes was required in either group and lung expansion outcomes were comparable. Conclusion Single chest tube drainage is slightly more effective than double chest tube drainage after decortication, with comparable outcomes and reduced invasiveness, suggesting its utility in clinical practice. Recommendation The researchers recommend that the post-traumatic chest tube insertion and care process be reviewed to lower the complication rate following chest trauma therapy using tube thoracostomy.